Partial Pole Placement in LMI Region - Liuli Ou; Shaobo Han; Yongji Wang; Shuai Dong; Lei Liu (Journal of Control Science and Engineering)
A new approach for pole placement of single-input system is proposed in this paper. Noncritical closed loop poles can be placed arbitrarily in a specified convex region when dominant poles are fixed in anticipant locations. The convex region is expressed in the form of linear matrix inequality (LMI), with which the partial pole placement problem can be solved via convex optimization tools. The validity and applicability of this approach are illustrated by two examples.